Exploitative Competition and Risk of Parasitism in Two Host Ant Species: The Roles of Habitat Complexity, Body Size, and Behavioral Dominance - Elliot B. Wilkinson; Donald H. Feener (Psyche: A Journal of Entomology)
Habitat structural complexity can slow resource discovery by ants but can also lower the risk of parasitism during foraging. The relative importance of these two ecological facets of habitat complexity may differ in a species-specific manner and thus may be important in the outcome of exploitative competition over food resources. For the host ant species Pheidole diversipilosa and P. bicarinata, we used in situ experimental manipulations to explore whether the effects of habitat complexity on exploitative competition depended on host body size and behavioral dominance, two characteristics likely to affect mobility and utilization of refuge from specialist Dipteran parasitoids (Apocephalus orthocladius and A. pugilist, resp.). We found that habitat complexity affected the resource discovery and harvest components of exploitative competition in an opposing fashion for each species and discuss these results in light of the differences in body size and behavioral dominance between the two hosts.